Vine Response to Water Stress Induced by Polyethylene Glycol - Van Zyl, J. L.; Kennedy, Catherine S. (South African Journal of Enology and Viticulture, 2017)
Polyethylene glycol (P E G) was used at different concentrations in glasshouse studies to create a range of solution osmotic potentials in an attempt to simulate the effect of water stress on vines. This was found to be a feasible technique provided that special precautions were taken to prevent P E G uptake and toxicity symptoms caused by mechanical root damage. Vine response in terms of transpiration, shoot elongation rate, stomata! resistance and leaf water potential, was monitored. Significant correlations were found between solution osmotic potential and all these parameters. Shoot growth was more sensitive than stomata! opening to osmotic potential which, in turn, correlated well with transpiration rate.